Optimalisasi Budaya Kerja 5S dan Standar Operasional Prosedur Praktikum - Sarwi Asri (JTEV (Jurnal Teknik Elektro dan Vokasional), 2021)
This study aims to determine the optimization of the application of 5S work culture and standard operating procedures for practicum in the Mechanical Engineering Education Study Program, Universitas Negeri Semarang. The research method used is an experimental method by comparing the conditions before and after implementing the 5S work culture and standard operational practicum procedures. The instrument used in this study was a questionnaire. This study shows that there is an increase in the performance aspect of 43.4%. Hypothesis testing shows that there is a better effect of the implementation of 5S work culture and standard operating procedures for practicum in the Mechanical Engineering Education Study Program, Universitas Negeri Semarang.